Convective Heat Transfer from Tube Banks of 8 Rows with Staggered Arrangements in Crossflow - Zol Amri, Ahmad Fikri Adli; Md Seri, Suzairin (Journal of Emerging Technologies and Industrial Applications, 2024)
This paper is studying about the ideal geometry of a crossflow heat exchanger under different ratio of pitch distances, by doing simulations on Computational Fluid Dynamics, CFD to observe the fluid flow characteristics and thermal characteristics. The aim of this study is to find a relationship between the thermal performance of crossflow tubular heat exchangers in staggered configurations and the flow geometry. The performance of heat exchanger are measured by how much heat being transferred. To increase the rate of heat transfer of the heat exchanger, one can simply increase the surface area of the fluid contact which in this case the surface area of a cylindrical tube. Those characteristics are determined by applying a number of varying inputs which consist of different Reynolds number, velocity and temperature in the CFD domain. The pressure coefficient, Cp, Nusselt number, Nu, and the efficiency are the main output data that will be used to validate and correlate this study. the efficiency of the crossflow heat exchanger will decrease when the ratio of the pitch distance increased. Besides that, the higher the Reynolds number, the lower the efficiency of the crossflow heat exchanger.